2011
DOI: 10.4103/1119-3077.86783
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and determinants of blood transfusion in a Nigerian neonatal unit

Abstract: The blood transfusion rate in this facility was remarkably high. Improved standard of newborn care and infrastructural support are required to reduce the transfusion rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 12 publications
5
13
1
Order By: Relevance
“…The clinical significance of this post ET drop in haematocrit was not stated and top up transfusion was not done. Contrary to the findings from the studies above [6][7][8], Ballot et al [9] from South Africa did not observe any significant change in haematocrit following double volume ET. Donor blood haematocrit is the major determinant of post ET haematocrit.…”
Section: Introductioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The clinical significance of this post ET drop in haematocrit was not stated and top up transfusion was not done. Contrary to the findings from the studies above [6][7][8], Ballot et al [9] from South Africa did not observe any significant change in haematocrit following double volume ET. Donor blood haematocrit is the major determinant of post ET haematocrit.…”
Section: Introductioncontrasting
confidence: 75%
“…This practice has however rarely been reported in the literature. In a retrospective review Volume 6 Issue 2 -2017 of neonatal transfusions over a period of 12 months at a teaching hospital in South West Nigeria, Ogunlesi et al [6] reported that 37 of 77 (49.3%) babies, who had exchange transfusion for severe neonatal jaundice, also received post exchange top up transfusion. The indications for these top up transfusions were however not stated.…”
Section: Introductionmentioning
confidence: 99%
“…Within the cesarean section–only studies, placenta previa at 27% (47 of 431) and obstructed labor at 25% (44 of 431) were the leading indications for transfusion. Among newborn babies, WB and RBC products were used in relatively equal measure, and neonatal jaundice and bleeding together accounted for 66% (218 of 477) of the products transfused overall …”
Section: Resultsmentioning
confidence: 99%
“…These 10 studies were used for the primary outcome calculation. The rest of the studies evaluated blood use among specific patient groups: nine studies among pediatric patients only; five on obstetrics and gynecology patients; three among cesarean section deliveries; three among newborn babies; two among elective surgical operations; two exclusively on the use of platelets; two on the use of autologous blood; and one among hepatogastroenterology patients . Most studies made a clear distinction between the number of patients transfused and the number of blood products used for transfusion.…”
Section: Resultsmentioning
confidence: 99%
“…Anaemia is a common morbidity in the neonatal intensive care unit (NICU) and this arises predominantly from frequent iatrogenic blood draws necessitated by the need for laboratory investigations and monitoring. The high prevalence of haemolytic conditions in Nigeria has also contributed to increased neonatal transfusion rates in the country [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%